2019
DOI: 10.1097/mcg.0000000000000992
|View full text |Cite
|
Sign up to set email alerts
|

Serum Pepsinogen as a Predictor for Gastric Cancer Death

Abstract: This long-term cohort study shows the usefulness of PG measurement as a biomarker that is specific to the risk of gastric cancer death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
2
13
1
1
Order By: Relevance
“…In CAG patients, we also noticed that our PGI level and PG I/PG II ratios are slightly higher when compared with other reports[ 9 - 12 ], and as all the CAG patients have histological confirmation, we therefore consider this effect could be due to patient population- or region-based variations, or might be due to variations from the degrees of atrophy itself. Future studies are required to explain these discrepancies.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In CAG patients, we also noticed that our PGI level and PG I/PG II ratios are slightly higher when compared with other reports[ 9 - 12 ], and as all the CAG patients have histological confirmation, we therefore consider this effect could be due to patient population- or region-based variations, or might be due to variations from the degrees of atrophy itself. Future studies are required to explain these discrepancies.…”
Section: Discussionsupporting
confidence: 62%
“…Application of G-17, PG I, PG II levels and PG I/PG II ratios in gastric cancer epidemiology study have been reported extensively, although their predicative values in stepwise gastric disease in clinical studies have not been very well defined. Previous investigations have generated inconsistent conclusions[ 9 - 12 ], and our results using AUROC analysis (Figure 2 ) indicated relatively low predictive value range from 0.529-0.786 for PU, CAG and GC patients, and type I H. pylori infection is the major factor that affects their levels as the disease progresses. These data provide insight to evaluate their application during clinical practice and are helpful in explaining the results.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Owing to the high risk of gastric cancer in this population, an initial screening programme was implemented in 1995-1998 based on pepsinogen measurements. 20 Mass screening and eradication of H. pylori were launched in 2004, the short-term benefits were evaluated in 2008, and the programme has been fully implemented on a biennial basis since 2012. Repeated screening was done to deal with the dynamic nature of this cohort and the observed increase in eligible subjects.…”
Section: Study Population and Preventive Programmementioning
confidence: 99%